2011
DOI: 10.1590/s0004-282x2011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric comorbidities in temporal lobe epilepsy in a Southern Brazilian population

Abstract: A great prevalence of psychiatric disorders in epilepsy is well demonstrated, although most studies have used unstructured psychiatric interviews for diagnosis. Here we present a study evaluating the prevalence of psychiatric comorbidities in a cohort of Southern Brazilian patients with temporal lobe epilepsy (TLE) using a structured clinical interview. We analyzed 166 patients with TLE regarding neuropsychiatric symptoms through the Structured Clinical Interview for DSM-IV. One hundred-six patients (63.9%) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 27 publications
6
36
3
5
Order By: Relevance
“…There are several other studies which show similar prevalence rates of psychiatric disorders in epilepsy, such as 58% by Adams et al, 18 41% by Gaitatzis et al, 7 and 37% by Davies et al 19 Fourteen percent of patients were diagnosed with an anxiety disorder, the most common diagnosis being panic disorder without agoraphobia. In this study, the overall anxiety findings were found to be lower compared with previous published rates of anxiety disorders in large population using SCIDs: 18.4, 20 21.5, 14 and 52.1%. 21 Whereas many patients with epilepsy experience anxiety or panic-type symptoms preictally or as part of an aura, the use of the SCID identifies those with true panic disorder, i.e., panic symptoms occurring unexpectedly and not due to the direct physiological effect of a GMC.…”
Section: Discussioncontrasting
confidence: 86%
“…There are several other studies which show similar prevalence rates of psychiatric disorders in epilepsy, such as 58% by Adams et al, 18 41% by Gaitatzis et al, 7 and 37% by Davies et al 19 Fourteen percent of patients were diagnosed with an anxiety disorder, the most common diagnosis being panic disorder without agoraphobia. In this study, the overall anxiety findings were found to be lower compared with previous published rates of anxiety disorders in large population using SCIDs: 18.4, 20 21.5, 14 and 52.1%. 21 Whereas many patients with epilepsy experience anxiety or panic-type symptoms preictally or as part of an aura, the use of the SCID identifies those with true panic disorder, i.e., panic symptoms occurring unexpectedly and not due to the direct physiological effect of a GMC.…”
Section: Discussioncontrasting
confidence: 86%
“…These authors reported that individuals with epilepsy were more likely than individuals without epilepsy to report lifetime anxiety disorders or suicidal thoughts [4]. In our patients with temporal lobe epilepsy (TLE), we observed high levels of psychiatric comorbidities, and our results are comparable to those reported for European populations [5,6]. Some data suggest that genetic and anatomically common neural networks might merge together leading to the development of psychiatric comorbidities in epilepsy [7][8][9][10].…”
Section: Introductionsupporting
confidence: 79%
“…However, most of this research has been limited to the investigation of selective samples, such as refractory mesial temporal sclerosis (MTS) and juvenile myclonic epilepsy (JME) [9,10], temporal lobe epilepsy (TLE) [11], and refractory focal epilepsy [12][13][14]. Collectively, these more recent studies have reported rates of mood disorders ranging from 25% to 48% and anxiety disorders from 14% to 31%.…”
Section: Introductionmentioning
confidence: 99%